Conservative treatment of corpus callosum hemorrhage due to a falling coconut in Indonesia: a case report - Hanan Anwar Rusidi; Ferry Wijanarko (Journal of Trauma and Injury)
The potential for traumatic brain injury resulting from falling coconuts is frequently overlooked. These incidents can cause focal lesions in the form of brain hemorrhage. Corpus callosum hemorrhage due to blunt trauma from a falling object is rare and typically associated with poor prognosis. The purpose of this report is to detail a case of corpus callosum hemorrhage caused by a coconut fall and to discuss the conservative management approach employed. We report the case of a 54-year-old woman who was admitted to the hospital with symptoms of unconsciousness, headache, and expressive aphasia after being struck by a falling coconut. Notably, hemorrhage was detected within the body of the corpus callosum, as revealed by imaging findings. The patient received intensive monitoring and treatment in the intensive care unit, including oxygen therapy, saline infusion, an osmotic diuretic, analgesics, and medication to prevent stress ulcers. The patient demonstrated marked clinical improvement while undergoing conservative treatment. Despite the typically unfavorable prognosis of these rare injuries, our patient exhibited meaningful clinical improvement with conservative treatment. Timely diagnosis and appropriate interventions were crucial in managing the patient’s condition. This report emphasizes the importance of considering traumatic brain injury caused by falling coconuts and highlights the need for further research and awareness in this area.